EFFECTIVENESS OF PEPPERMINT-CITRUS AROMATHERAPY INHALERS IN REDUCING EMESIS GRAVIDARUM AMONG FIRST-TRIMESTER PREGNANT WOMEN - Wijayanti, Erna Eka; Qonitun, Umu; Hurin'in, Nur Maziyah; Khoir, Violetta Dity Virginia; Rahmawati5 , Eva Silviana (UNIVERSITAS AIRLANGGA, 2025)
Background: Aromatherapy is recognized as an effective, safe, and natural method for alleviating nausea-vomiting in pregnancy. The most prevalent physiological discomforts encountered during early gestation is nausea and vomiting of pregnancy (NVP), frequently termed